Health Equity and Human Papillomavirus Vaccine Interventions for Adolescents: A Systematic Review - Sarah B. Maness; Lois Coleman Carpenter; Idara Akpan; Nubwa St. James; Daniela Romero-Cely; G. J. Corey Harmon; Miranda Cano; Erika L. Thompson (Vaccines)
Background/Objectives: Human papillomavirus (HPV) causes multiple types of cancer, and demographic-based inequities in HPV-related cancers persist. Behavioral interventions have increased HPV vaccination uptake, yet it is unclear how intervention effects vary by demographics. The purpose of this study was to examine whether existing HPV vaccine interventions for adolescents have unequal effects on HPV vaccine uptake. Methods: We searched MEDLINE via PubMed, PsycINFO, CINAHL, Scopus, and Cochrane CENTRAL in October 2023. The search strategy combined keywords and subject terms for HPV vaccine, interventions/health promotion, and adolescents. Studies were included in final analyses if they were peer-reviewed, published in the US between 2006 and 2023, included outcome measures from an evidence-based HPV vaccination intervention, included adolescents aged 9–17, and demographic variables for age, race/ethnicity, income/SES, or geographic region. Studies were excluded if they were review articles, abstract-only, dissertations or theses, non-English language, non-US-based, or outside the age range of 9–17. Studies were also excluded if they did not include an intervention, outcome evaluation measures, or demographic measures. The screening and extraction processes were independently performed by multiple reviewers using Covidence software. Results: Ultimately, 74 articles were included for full extraction. Sex was the most common demographic variable analyzed by the HPV vaccine (n = 38), followed by race/ethnicity (n = 15), income/SES (n = 6), and geographic region (n = 6). Conclusions: Few interventions assess whether intervention results differ by demographics, making it unclear whether these interventions reduce health inequities. This review included a wide variation in study designs, limiting our ability to uniformly assess study conclusions.